Possibilities of Creating Swimming Pools with Zero Co2 Emissions Due to Energy Use in Them - Vourdoubas, John (Asian Journal of Energy Transformation and Conservation, 2017)
Swimming pools consume large amounts of energy compared with various buildings. Most of them utilize conventional fuels for covering their heating and electricity needs. Increase of their sustainability could be achieved with the replacement of conventional fuels with renewable energies. The possibility of using only renewable energies for covering all their energy requirements has been examined. Solar thermal energy, solid biomass and low enthalpy geothermal energy with heat pumps could cover their heating needs. Solar-PV energy could generate the necessary electricity in the pool. Investigation of the possibility of using different combinations of the abovementioned renewable energies in swimming pools indicate that they could cover all their energy needs zeroing their CO2 emissions and their carbon footprint due to energy use. These renewable energy technologies are also reliable, mature and cost effective. A case study in Crete, Greece has been implemented indicating that an investment in renewable energy systems of 1,072 to 1,474 € per m2 of pool would achieve reduction of 1,538 kg CO2 per m2 of pool zeroing their CO2 emissions. A significant decrease of the operating cost of the swimming pool due to lower fuel cost would be also achieved offering an attractive payback period of the investment.